Congenital vascular tumor of difficult classification - Troia, M.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2017)
This case demonstrates how difficult it can be at least initially to diagnose a dermatological lesion both clinically and histologically. At birth, the clinical appearance of an ulcerated hard tumor seemed to suggest a malignant sarcoma. The histological examination excluded the worst hypothesis and ascertained the lymphatic vascular nature of the lesion; however, it was unable to differentiate between a low grade malignant tumor and a malformation. Dabska’s tumor (5) is a low grade angiosarcoma characterized by intralymphatic endothelial proliferation, so it is also referred to as PILA – papillary intralymphatic angioendothelioma – (6); Calonje’s retiform hemangioendothelioma (4), so called for the vascular anastomosis characteristics that recall the testis network, is also a low-grade angiosarcoma similar to PILA; instead, hemosiderotic targetoid hemangioma (8) is a lymphatic malformation (2) clinically characterized by a peripheral ecchymosis and histologically by the presence of extravasated red-blood cells in various evolutionary phases. Progressive acquired lymphangioma (7) is a slowly progressive acquired characteristic tumor of the adult. Long-term clinical observation favored the diagnosis of lymphatic malformation and allowed the hypothesis of intra- and peripheral hemorrhage, possibly related to the trauma of delivery; the hemorrhage could explain along with the reactive flogosis the particular infiltration at birth, regressed over the months with the characteristic chromatic variations. Against the diagnosis of lymphatic malformation type hemosiderotic targetoid hemangioma is the size of the lesion, but in the literature there are other similar congenital cases affecting the knee (1, 3).